2005
DOI: 10.1299/jsmea.48.335
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Analysis of Surface Crack in Rolling and Wire Drawing

Abstract: The surface flaw of a drawn wire has a significant influence on the quality of a product. High-surface-quality drawn wires and rods have been required for the manufacture of automobiles and machines. Wire breaks due to large surface defects are common problems in wire drawing. The authors carried out rolling and multi-pass drawing of a stainless-steel wire with an artificial scratch, and investigated the growth and disappearance of a scratch from both sides by experiments and Finite Element Analysis (FEA). Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
1
7
0
Order By: Relevance
“…Meanwhile, the shape of the surface flaw was somewhat different with R h per pass. For example, a larger R h per pass led to a smaller d and larger w. It is well known that the surface flaw becomes sharp with increasing d and decreasing w, leading to a higher risk of fracture caused by the surface flaw, 6,9,14) especially in cold forming processes. Therefore, the r value is defined as the ratio of the depth and width of the surface flaw in this study.…”
Section: Validation Of Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the shape of the surface flaw was somewhat different with R h per pass. For example, a larger R h per pass led to a smaller d and larger w. It is well known that the surface flaw becomes sharp with increasing d and decreasing w, leading to a higher risk of fracture caused by the surface flaw, 6,9,14) especially in cold forming processes. Therefore, the r value is defined as the ratio of the depth and width of the surface flaw in this study.…”
Section: Validation Of Numerical Simulationmentioning
confidence: 99%
“…7) Therefore, we need to understand the deformation behavior of surface flaws during downstream forming processes such as hot rolling, wire drawing, flat wire rolling, and forging. Several studies have been conducted regarding the deformation behavior of surface flaws during the hot rolling, 2,4,[8][9][10][11][12] wire drawing 6,[13][14][15][16] and forging processes. 17,18) However, no literature can be found concerning the deformation behavior of surface flaws during the flat wire rolling process although flat-rolled wires are used in many applications, such as windshield wipers, springs, guide rails, and saw blades.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies on the deformation behavior of surface flaw during wire drawing process. Shinohara and Yoshida 5,14) reported that a crack with a small angle become smaller during repeated wire drawing in stainless steel. They showed that the surface crack becomes an overlap type flaw as the crack angle is smaller, whereas the bottom of crack rises and thus disappears when the crack angle is large.…”
Section: Effects Of Process Conditions Materials Properties and Initial Shape Of Flaw On The Deformation Behavior Of Surface Flaw During mentioning
confidence: 99%
“…They reported that the shape of deformed surface flaw depends on the initial shape of flaw and it is independent of the material properties such as Cu, Al, and low carbon steel wires. Most of the papers were focused on the shape of surface defect, and only a few studies have considered the process conditions 5) and material properties 16) during wire drawing. In addition, the literature still lacks a systematic study to find the optimum parameters to remove or reduce the surface flaw during wire drawing process.…”
Section: Effects Of Process Conditions Materials Properties and Initial Shape Of Flaw On The Deformation Behavior Of Surface Flaw During mentioning
confidence: 99%
See 1 more Smart Citation